High-quality genome assembly of Verticillium dahliae VD991 allows for screening and validation of pathogenic genes - Yang, Jiaxiang; Liu, Lisen; Yang, Lan; Liu, Renju; Gao, Chenxu; Hu, Wei; Yan, Qingdi; Yang, Zhaoen; Fan, Liqiang (Frontiers in Microbiology, 2023)
Verticillium dahliae (V. dahliae) is a notorious soil-borne pathogen causing Verticillium wilt in more than 400 dicotyledonous plants, including a wide range of economically important crops, such as cotton, tomato, lettuce, potato, and romaine lettuce, which can result in extensive economic losses. In the last decade, several studies have been conducted on the physiological and molecular mechanisms of plant resistance to V. dahliae. However, the lack of a complete genome sequence with a high-quality assembly and complete genomic annotations for V. dahliae has limited these studies. In this study, we produced a full genomic assembly for V. dahliae VD991 using Nanopore sequencing technology, consisting of 35.77 Mb across eight pseudochromosomes and with a GC content of 53.41%. Analysis of the genome completeness assessment (BUSCO alignment: 98.62%; Illumina reads alignment: 99.17%) indicated that our efforts resulted in a nearly complete and high-quality genomic assembly. We selected 25 species closely related to V. dahliae for evolutionary analysis, confirming the evolutionary relationship between V. dahliae and related species, and the identification of a possible whole genome duplication event in V. dahliae. The interaction between cotton and V. dahliae was investigated by transcriptome sequencing resulting in the identification of many genes and pathways associated with cotton disease resistance and V. dahliae pathogenesis. These results will provide new insights into the pathogenic mechanisms of V. dahliae and contribute to the cultivation of cotton varieties resistant to Verticillium wilt.